2015
DOI: 10.5194/acp-15-4339-2015
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying pyroconvective injection heights using observations of fire energy: sensitivity of spaceborne observations of carbon monoxide

Abstract: Abstract. We use observations of active fire area and fire radiative power (FRP) from the NASA Moderate Resolution Imaging Spectroradiometers (MODIS), together with a parameterized plume rise model, to estimate biomass burning injection heights during 2006. We use these injection heights in the GEOS-Chem (Goddard Earth Observing System Chemistry) atmospheric chemistry transport model to vertically distribute biomass burning emissions of carbon monoxide (CO) and to study the resulting atmospheric distribution. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 81 publications
3
19
0
Order By: Relevance
“…The general CALIOP uncertainties in AOT profiles (e.g., Kacenelenbogen et al, 2011;Ma et al, 2013) exceed by far the uncertainties in emission heights. A minor general importance of emission heights compared to the large uncertainties in the emission inventories has also been found by Gonzi et al (2015) for CO emissions. net forcing net solar radiative forcing net thermal radiative forcing net forcing net solar radiative forcing net thermal radiative forcing Table 1.…”
Section: Caliopmentioning
confidence: 94%
See 1 more Smart Citation
“…The general CALIOP uncertainties in AOT profiles (e.g., Kacenelenbogen et al, 2011;Ma et al, 2013) exceed by far the uncertainties in emission heights. A minor general importance of emission heights compared to the large uncertainties in the emission inventories has also been found by Gonzi et al (2015) for CO emissions. net forcing net solar radiative forcing net thermal radiative forcing net forcing net solar radiative forcing net thermal radiative forcing Table 1.…”
Section: Caliopmentioning
confidence: 94%
“…For a study by Stein et al (2009), in one case PBL injections performed best, whereas in another case plume heights up to 3 km were necessary to reproduce observations. Gonzi et al (2015) applied a modified version of the 1-D plume model by Freitas et al (2007), Moderate Resolution Imaging Spectroradiometer (MODIS) fire radiative power (FRP) and fire size to simulate global CO concentrations in GEOS-Chem for the year 2006. The authors compared modeling results to MOPITT (Measurement of Pollution in the Troposphere) satellite data, but it turned out that the particular emission height impact on the overall bias was not quantifiable.…”
Section: A Veira Et Al: Impact On Transport Black Carbon Concentramentioning
confidence: 99%
“…In this case, it can no longer be assumed that the aerosol above a location of the fire is vertically well mixed. Gonzi et al (2015) applied a one-dimensional plume rise model in global-scale GEOS-Chem simulations during the year 2006. They concluded that approximately 80 % of the injections of biomass burning aerosol occur below the boundary layer height.…”
Section: Plume Heightsmentioning
confidence: 99%
“…However, for a more complete representation of the source fires, many CTMs can also make use of information on the altitude at which the bulk of the emitted species is injected into the wider atmosphere, where they can fully interact with ambient atmospheric circulation. In a recent study on fire emission transport Gonzi et al (2015) use the GEOS-Chem CTM with a horizontal resolution of 2 • × 2.5…”
mentioning
confidence: 99%